Volume 2: Turbo Expo 2005 2005
DOI: 10.1115/gt2005-68085
|View full text |Cite
|
Sign up to set email alerts
|

Ejectors Design in the Rolls-Royce 1MW Hybrid System

Abstract: Rolls-Royce Fuel Cell Systems Limited in the last few years has been developing a low cost hybrid system for electricity production based on planar SOFCs (Solide Oxide Fuel Cells). The novel cycle is based on the recycle of cathodic off-gas to pre-heat the oxidant flow, using ejectors. On the anode side, ejectors are used to recycle steam-rich off-gas to the reforming reactor. This paper describes the analysis process carried out to optimize the ejector geometry, from the preliminary sizing of lengths and sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…constraints to be considered [8]. For instance, an anodic ejector has to ensure very high values of the recirculation factor (F) to avoid depositing carbon in the anodic circuit, even at off-design and transient conditions [9], and the main role of the cathodic ejector is to perform the required recirculation without excessive pressure difference between the compressor outlet and turbine inlet [10].…”
Section: Gt2006-90447mentioning
confidence: 99%
See 1 more Smart Citation
“…constraints to be considered [8]. For instance, an anodic ejector has to ensure very high values of the recirculation factor (F) to avoid depositing carbon in the anodic circuit, even at off-design and transient conditions [9], and the main role of the cathodic ejector is to perform the required recirculation without excessive pressure difference between the compressor outlet and turbine inlet [10].…”
Section: Gt2006-90447mentioning
confidence: 99%
“…In previous works [8,10,11] the ejectors for hybrid system applications were studied at steady-state conditions from both theoretical and experimental points of view. In fact, in [11] the authors have shown a new design procedure based on 0-D and 2-D/3-D CFD models, successfully validated with the experimental results obtained with the closed-loop ejector-test rig developed at University of Genoa [3,10].…”
Section: Figure 2 Anodic Ejector Layoutmentioning
confidence: 99%
“…It is composed of a nozzle and a mixing duct (Fig. Recently, ejectors have been also considered for fuel recirculation in fuel cell vehicles [3,4]. Ejectors have several advantages, including its simplicity, reliability, and durability.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained mesh quality was about 0.5. This mesh was selected after some preliminary calculations to obtain a good solution independence from the grid [27,28]. Theses preliminary simulations showed about 13% change in the recirculation ratio (in comparison with the chosen approach) for a mesh composed of 252,000 cells and no significant variations for values higher than 500,000 cells.…”
mentioning
confidence: 99%
“…The turbulence model was chosen considering previous CFD calculations on ejectors: in[6] the authors demonstrated (on the basis of a comparison with the Large the Eddy Simulation tool and on results shown in[11]) that the k-epsilon model is an acceptable compromise between the solution accuracy and the calculation time (in agreement with the objectives of this study). For the inlet boundary conditions of the turbulence model, the Fluent default values were used (5% turbulent intensity, 10 turbulent viscosity ratio)[27,28]. According with a preliminary analysis, these values had a negligible effect on the results.…”
mentioning
confidence: 99%